Whole genome sequencing reveals mycobacterial microevolution among concurrent isolates from sputum and blood in HIV infected TB patients. Issue 1 (December 2016) - Ssengooba, Willy; de Jong, Bouke; Joloba, Moses; Cobelens, Frank; Meehan, Conor
Abstract Background In the context of advanced immunosuppression, M. tuberculosis is known to cause detectable mycobacteremia. However, little is known about the intra-patient mycobacterial microevolution and the direction of seeding between the sputum and blood compartments. Methods From a diagnostic study of HIV-infected TB patients, 51 pairs of concurrent blood and sputumM. tuberculosis isolates from the same patient were available. In a previous analysis, we identified a subset with genotypic concordance, based on spoligotyping and 24 locus MIRU-VNTR. These paired isolates with identical genotypes were analyzed by whole genome sequencing and phylogenetic analysis. Results Of the 25 concordant pairs (49 % of the 51 paired isolates), 15 (60 %) remained viable for extraction of high quality DNA for whole genome sequencing. Two patient pairs were excluded due to poor quality sequence reads. The median CD4 cell count was 32 (IQR; 16–101)/mm3 and ten (77 %) patients were on ART. No drug resistance mutations were identified in any of the sequences analyzed. Three (23.1 %) of 13 patients had SNPs separating paired isolates from blood and sputum compartments, indicating evidence of microevolution. Using a phylogenetic approach to identify the ancestral compartment, in two (15 %) patients the blood isolate was ancestral to the sputum isolate, in one (8 %) it was the opposite, and ten (77 %) of the pairs were identical. Conclusions Among HIV-infected patients with poor cellular immunity, infection with multiple strains ofM. tuberculosis was found in half of the patients. In those patients with identical strains, whole genome sequencing indicated thatM. tuberculosis intra-patient microevolution does occur in a few patients, yet did not reveal a consistent direction of spread between sputum and blood. This suggests that these compartments are highly connected and potentially seed each other repeatedly.